Accounting Information System: Revenue Cycle on Clothing Company - Badar Fitrawan, Noerlina (International Journal of Advanced Science and Technology, 2020)
The purpose of this research is to analyze ongoing problems that often occur and also to design accounting information systems from the revenue cycle. The results of the analysis tell that there is a need for an accounting information system for revenue cycle that can integrate company’s business process, so that all transaction data can be found and stored properly. As this accounting information system is created, it is expected to reduce problems such as data lost and the risk of fraud due to creating documents manually. The method that is use based on the problems that have been found to a business process design is created by using Object Oriented Analysis and Design (OOAD) which is illustrated through the Unified Modeling Language (UML) diagram notation. The proposed of the business process design provides solutions to the problems in revenue cycle by creating a system that includes cash and credit sales, return of goods, and making reports that can work quickly and accurately to improve the performance with the integrated systems.Keywords: Analysis, Design, Accounting Information Systems, Revenue Cycle